2015
DOI: 10.17795/nmsjournal27001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melissa officinalis Capsule on the Intensity of Premenstrual Syndrome Symptoms in High School Girl Students

Abstract: Background:Several studies are conducted on Premenstrual Syndrome (PMS). However, a few herbal surveys exist on the treatment of PMS in Iran. Due to the sedative effects of Melissa officinalis (M. officinalis), this question comes to mind that “can it be used in the treatment of PMS symptoms?”Objectives:The current study aimed to assess the effect of M. officinalis capsule on the intensity of PMS in high-school girls.Materials and Methods:A double-blind randomized, placebo-controlled trial was performed on 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Several similar studies with other laboratory‐based paradigms have also reported improvements from M. officinalis , which are consistent with anxiolytic‐like effects (Kennedy et al, ; Kennedy, Little, & Scholey, ; Scholey et al, ). Finally, a double‐blind RCT in 100 school age females (Akbarzadeh et al, ) reported efficacy of 1200 mg of M. officinalis extract daily over 3 months for reducing stress and tension associated with premenstrual dysphoric disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Several similar studies with other laboratory‐based paradigms have also reported improvements from M. officinalis , which are consistent with anxiolytic‐like effects (Kennedy et al, ; Kennedy, Little, & Scholey, ; Scholey et al, ). Finally, a double‐blind RCT in 100 school age females (Akbarzadeh et al, ) reported efficacy of 1200 mg of M. officinalis extract daily over 3 months for reducing stress and tension associated with premenstrual dysphoric disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, premenstrual syndrome as the periodical recurrence of a set of annoying physical, mental, and behavioral disorders in the luteal phase of menstrual cycle is a burden on quality of life in adolescents (19,20). Especially, increased severity in PMS symptoms results in decreased quality of mental health, reduced work productivity and more workdays missed for health reasons (21).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the changes in the quality of life, self-esteem might be affected. Besides, Akbarzadeh et al revealed that "In Iran, it has been estimated that 98.2% of female university students averagely or severely experience at least one of the PMS symptoms at the age 18 -27 years" (20).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, previous studies into of the effects of aromatherapy on the social functions of PMS have been limited, with some articles having reported that Melissa officinalis in capsule form was associated with reduced severity of physical, mental and social symptoms . It should be noted that ameliorating physical and mental symptoms of PMS could be expected to improve social functions.…”
Section: Discussionmentioning
confidence: 99%